The Role of Digital Communication in Promoting Civic Participation: Moroccan platform I share a model - Filali, Zineb Sadouk (Journal of Humanities & Social Sciences, 2025)
The study examines the role of digital communication in enhancing individual civic engagement, given the evolution of the digital communication environment and the expansion of its integration by national bodies and public institutions. The goal is to create a dynamic of civic engagement with various social actors, and to leverage the features and characteristics of digital communication platforms in its strategies. They have become spaces for knowledge production and the exchange of opinions within a participatory approach that seeks joint construction and effective contribution to the management of public affairs.The study assumes that digital communication platforms are technological communication channels for establishing advisory mechanisms to promote citizen participation, both male and female, with the goal of achieving positive engagement in public decision-making.In this context, the study concluded that these collaborative platforms are capable of absorbing and exercising the functions of information, guidance, and influence for the benefit of young people involved in these digital platforms. The challenge of enhancing the level of civic participation within society remains tied to the extent to which public institutions respond to the results of citizen consultations, which reflect growing societal awareness of current issues and express the daily living needs of Moroccan citizens.
Keywords: Digital communication; Communication platforms; Citizen participation; Digital transformation